Faktor-Faktor Yang Mempengaruhi Penggunaan Teknologi Sistem Informasi Pembangunan Daerah (Sipd) - adhyatmaka, dhafy; Novianti, Nurlita (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2023)
This study aims to examine the effect of performance expectations, effort expectations, social influence, and facilitating conditions on the intention to use the Regional Development Information System (SIPD) and to examine the effect of facilitating conditions and the intention to use SIPD on the use of SIPD utilizing quantitative approach. The population in this study includes all financial management employees of the Regional Financial and Asset Management Agency (BKAD) of Blitar Regency Government, from which 39 samples are selected through purposive sampling, and the data are collected from a survey and questionnaires and analysed by Partial Least Square (PLS) utilizing SmartPLS. The study's results revealed that performance expectations and effort expectations did not affect the intention to use SIPD; social influences and facilitating conditions affected the intention to use SIPD; and facilitating conditions affected the use of SIPD, yet the intention to use did not affect the use of SIPD.